Lessons for Asia from Europe's history with banking integration - Douglas J. Elliott (Asian Development Bank Institute (ADBI), 2014)
As Asia considers greater harmonization and integration of its financial systems, it would be well-advised to consider the experience of Europe, particularly the eurozone. There are many lessons to be drawn from Europe about how to implement such integration, mostly negative. It is particularly evident that moving to a currency union had major unanticipated consequences for the ability to manage integration of financial systems within the eurozone. Monetary union sharply reduced the ability of the member states of the eurozone to manage their macroeconomic and macroprudential policies to preserve financial stability. Even setting aside these additional problems created by monetary union, Europe suffered substantial harm from integrating its financial systems so closely in many ways, while simultaneously establishing only very weak coordinating mechanisms among their national financial supervisors. It was also a mistake to forbid the European Central Bank from operating formally as a lender of last resort in a financial crisis. Europe's experiences should not dissuade Asia from seeking appropriate further harmonization and integration. However, they do argue strongly for Asia to take the kind of careful, step-by-step, long-term approach for which many of the countries within Asia are well known. In particular, Asia should only move forward to the extent that it is willing to take the necessary steps toward common supervisory approaches, information sharing, and cooperation in crises. Trying to have the benefits of integration without the responsibilities would be a recipe for future disaster.
Keywords: E44; F15; F36; 330; harmonization; integration; eurozone; asia; european union